3D coordinate transformation using molodensky badekas transformation model: MBT07 - Phang, Seng Boon; Setan, Halim (2007)
Transformations between coordinate systems are routinely carried out in surveying. As satellite positioning techniques are more frequently used, transformations of three-dimensional (3D) coordinates will become a common practice. The main objective of this research is to develop a computer program (using Visual Basic 6.0) to determine the 7 parameters used in 3D coordinate transformations. The derived parameters are then back substitute into the transformation equation to perform coordinate transformation. The developed program is called Molodensky Badekas Transformation 2007 (MBT07). MBT07 was developed based on one of the most common transformation model for 3D coordinates which is Molodensky Badekas transformation model. Another short program was developed with MATLAB, to confirm the algorithms involved in Molodensky Badekas transformation before creating MBT07. The third software that is involved in this research is Geodetic Datum Transformation Suite (GDTS). This software is used to validate the computed results from MBT07 and MATLAB. Two sets of data were used for testing GDTS, MBT07 and MATLAB. The datasets contained coordinates of common points in two coordinate systems. The parameters derived from MBT07 and MATLAB are compared with the results obtained from GDTS. Even though the analysis shows a small difference for the parameters, it is still within the permitted standard deviation. Besides calculating parameters, MBT07 also contains three other modules related to transformation.